PEMBELAJARAN SOMATIK AUDITORI VISUAL INTELEKTUAL (SAVI) DENGAN MEDIA COMPACT DISC INTERAKTIF (Jurnal Inovasi Pendidikan Kimia, 2013)
This study aimed to find out the influence of the Somatic Auditory Visual Intellectual (SAVI) learning model application by using CD interactive as media toward the hydrocarbon subject for the X grader of a Senior High School in Kudus for academic year of 2011/2012. The population of this study was X-3 up to X-10 class. Cluster random sampling technique was used to take the sample, and the result showed that X-10 was the experimental class and X-9 was the control one. Hypothesis test used biserial correlation and determination coefficient. This study showed that the cognitive score average of experimental class was 83.53 where as the control one was 78.09. The influence of cognitive learning outcomes was suitable with the biserial correlation coefficient 0.48 and the determination coefficient 22.94% with medium criterion. Influence of the affective and psycomotoric were showed descriptively from the average score of experimental class which was better than control one. The checklist proved that the students responses toward SAVI learning model application using CD interactive as media were good. From this study, it can be concluded that toward SAVI learning model application using CD interactive as media influence the students result in learning hydrocarbon material.Key Word: SAVI Learning Model